Refining English tutors' skills: Documentary films as pre-teaching reference (Englisia : Journal of Language, Education, and Humanities, 2024)
Training spoken English tutors requires a variety of resources, including audio-visual references. However, popular social media tutorials often focus on teaching specific English materials, neglecting broader teaching techniques. Ideal tutors need a positive and engaging personality, knowledge transfer strategies, adaptable approaches to classroom conditions, meticulous preparation, and effective wrap-up activities - elements that are missing from most tutorial videos. This study investigates the potential of short documentary films as a reference for teaching techniques for 13 prospective tutors in an intermediate English class. Through an integrated mentoring program for the production of short documentaries, the study explores, describes and addresses the challenges of teaching preparation through observation, interviews and literature review. It also analyzes the potential of documentaries to support teaching and formulates criteria for effective documentary content relevant to teacher preparation. The findings suggest that integrating documentary film production into the English language teaching curriculum can equip tutors with the necessary skills for successful micro-teaching experiences. This approach allows tutors to create personalized short documentaries that serve as a reference for teaching techniques tailored to their specific pre-teaching needs. Tutors gain a deeper understanding and ability to demonstrate not only teaching techniques, but also classroom management elements such as preparation, wrap-up activities, brainstorming and teaching approaches.
Keywords: Documentary film; Film reference; Teaching techniques; Prospective tutors